Saliva and Serum Cytokine Profiles During Oral Ulceration in Behçet’s Disease - Novak, Tanya; Hamedi, Mojgan; Bergmeier, Lesley Ann; Fortune, Farida; Hagi-Pavli, Eleni (Frontiers in Immunology, 2021)
Behçet’s disease (BD) is a chronic, multi-systemic disorder of unknown aetiology typified by recurrent oral and genital mucocutaneous lesions, uveitis and vasculitis. Innate and adaptive immune system dysregulation has been implicated in pathogenesis with alterations in serum cytokine profiles. Few studies have investigated salivary cytokines in BD, despite more than 90% of BD patients first presenting with oral ulceration. The aim of this pilot study was twofold; firstly to investigate whether cytokine levels in matched serum and saliva samples show a differential profile in BD (with and without oral ulcers), recurrent aphthous stomatitis (RAS) and healthy controls (HCs), and secondly, to explore if any differential profiles in serum and/or saliva could provide a panel of cytokines with diagnostic and therapeutic potential for BD. Concentrations of 12 cytokines (IL-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12p70, IL-17A, IFN-γ, TNF-α, TNF-β) were measured using the Human Th1/Th2 11-Plex FlowCytomix™ kit with IL-17A, in BD (N=20), RAS (N=6) and HCs (N=10). A differential range of cytokines was detected in serum and saliva with the majority of cytokine levels higher in saliva. The most prevalent salivary cytokines were IL-1β, IL-2, IL-8, IL-10 and TNF-α present in all samples in contrast to serum where the most prevalent cytokine detected was IL-8 (91.9%). The least abundant cytokine was IFN-γ in both saliva (43.2%) and serum (2.7%). After normalizing saliva for protein content, BD patients with oral ulcers (BD-MA) had significantly higher levels of salivary IL-1β (p=0.01), IL-8 (p=0.02), TNF-α (p=0.004) and IL-6 (p=0.01) than HCs. Notably, BD patients without oral ulcers (BD-MQ) also had significantly higher salivary IL-1β, IL-8 and TNF-α (p ≤ 0.05) than HCs. During relapsed (BD-RE) and quiet (BD-Q) systemic episodes, salivary IL-β and TNF-α were also significantly increased with IL-8 significantly higher only in BD-Q (p=0.02). BD oral ulcers signify a potential reactivation of systemic inflammation. Identifying cytokines released during asymptomatic episodes and oral ulceration might lead to targeted drug therapy to prevent recurrent oral ulcers and possible disease relapse. This is the first study to report salivary cytokine levels in BD. The detectable levels suggests cytokine profiling of BD saliva may provide an alternative, less invasive, sensitive procedure for frequent monitoring of disease activity and progression.